A Critical Review of the Conceptualization, Operationalization, and Empirical Literature on Cognition‐Based and Affect‐Based Trust. (22nd March 2022) - Legood, Alison; van der Werff, Lisa; Lee, Allan; den Hartog, Deanne; van Knippenberg, Daan
Abstract: Trust plays a pivotal role in the development and maintenance of effective working relationships. In this paper we offer a critical review of the conceptualization and operationalization of cognition‐based and affect‐based trust. While definitions and measures of trust are abundant, the view of trust as a concept with cognitive and affective bases is well established. Nevertheless, the validity of this approach has rarely been examined. Our theoretical and empirical review (content validity study, systematic review and meta‐analysis) of the literature reveals a failure to fully capture cognition or affect in current trust theory and measurement. We find the construct of affect‐based trust to be particularly problematic in its current form. Resolving these issues is critical to advancing our understanding of the differentiating roles of these two important bases of trust. We detail areas for future research on the conceptualization and measurement of trust to stimulate theoretical exploration and methodological advances.